NiMn2O4 revisited: Temperature‐dependent cation distribution from in situ neutron diffraction and thermopower studies. Issue 3 (9th November 2022) - Dinger, Jan; Friedrich, Thomas; Reimann, Timmy; Töpfer, Jörg
Abstract: The cation distribution of the negative temperature coefficient (NTC) thermistor spinel NiMn2 O4 was studied in the temperature range from 55 to 900°C, using a combined in situ neutron diffraction and thermopower study. Rietveld refinements of in situ neutron diffraction data reveal a temperature dependence of the degree of inversion with an inversion parameter of 0.70(1) at 900°C and 0.87(1) at 55°C. Thermopower measurements were evaluated using a modified Heikes formula, and the [Mn 4+ ]/[Mn 3+ ] ratio on octahedral sites of the spinel structure was calculated considering spin and orbital degeneracy. The inversion degree and disproportionation parameter, determined independently as function of temperature, were used to calculate the cation distribution of NiMn2 O4 in the whole temperature range. At high temperature, within the stability range of the spinel, the cation distribution is characterized by a moderate degree of inversion with a concentration of Ni B 2 + Ni_B^2+ = 0.71(2) and small tendency toward disproportionation with a high concentration of Mn B 3 + Mn_B^3+ = 0.98(2). At 55°C, cation inversion is enhanced as illustrated by a large concentration of Ni B 2 + Ni_B^2+ = 0.87(2), and a small Mn B 3 + Mn_B^3+ = 0.24(2) content indicates extensive Mn‐disproportionation. Finally, conclusions regarding possible ageing mechanisms of this important NTC thermistor material are drawn.